Uptake of evidence-based practice and its predictors among nurses in Ethiopia: a systematic review and meta-analysis - Wudu, Muluken Amare; Tarekegn, Setegn Mihret; Wondifraw, Endalk Birrie; Birhanu, Tarikua Afework; Hailu, Molla Kassa; Bekalu, Yemane Eshetu; Yosef, Selamyhun Tadesse; Belete, Melaku Ashagrie (Frontiers in Pharmacology, 2024)
Background: While evidence-based practice has demonstrated its capacity to enhance healthcare quality and bolster clinical outcomes, the translation of research into clinical practice encounters persistent challenges. In Ethiopia, there remains a dearth of comprehensive and nationally representative data concerning the extent of Evidence-based practice adoption among nurses.Thus, this systematic review and meta-analysis endeavors to assess the overall prevalence of Evidence-based practice implementation and delve into its determinants among Ethiopian nurses.Methods: A systematic review and meta-analysis were conducted following the PRISMA guidelines. In order to identify pertinent studies, a search was conducted across PubMed, Scopus, Google Scholar, and EMBASE databases. A weighted inverse variance random-effects model was employed to estimate the pooled prevalence. Cochrane's Q-test and I 2 statistics were calculated to assess heterogeneity among studies. Funnel plots and Egger's test were utilized to evaluate publication bias. Pooled implementation rates and meta-regression analysis were carried out using STATA 17.Results: Of the total 1590 retrieved articles, twelve studies including 4933 nurses were included in the final analysis. The pooled prevalence of Evidence-based practice uptake among nurses in Ethiopia is 53% (95% CI: 46%-60%). Having knowledge about Evidence-based practice (AOR=2.29; 95% CI: 1.90, 2.69; I 2 =70.95%), holding a favorable attitude towards Evidence-based practice (AOR=2.56; 95% CI: 1.63, 3.49; I2=88.39%), occupying a head nurse position (AOR=3.15; 95% CI: 1.85, 4.46; I 2 =87.42%), possessing effective communication skills (AOR=4.99; 95% CI: 1.47, 8.51; I 2 =99.86%), and having access to Evidence-based practice guidelines (AOR=1.90; 95% CI: 1.55, 2.24; I 2 =57.24%) were identified as predictors of the uptake of Evidence-based practice.Only half of Ethiopia's nurses exhibit a strong embrace of Evidence-Based Practice within clinical settings, underscoring the urgent necessity for coordinated endeavors to cultivate this essential practice. Possessing knowledge, effective communication skills, access to updated guidelines, maintaining a positive attitude towards Evidence-Based Practice, and holding a position as head nurse emerged as predictors of successful implementation of Evidence-Based Practice. Hence, policymakers must prioritize capacity-building initiatives, disseminate the latest EBP guidelines widely, and strengthen mentorship roles for head nurses.